2003
DOI: 10.1093/sleep/26.6.695
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Exposure to Bright Light, as Compared to Dim Light, Decreases Sleepiness and Improves Psychomotor Vigilance Performance

Abstract: Daytime bright light exposure can reduce the impact of sleep loss on sleepiness levels and performance, as compared to dim light. These effects appear to be mediated by mechanisms that are separate from melatonin suppression. The results may assist in the development of treatments for daytime sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
242
7
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(287 citation statements)
references
References 0 publications
31
242
7
7
Order By: Relevance
“…Our PVT data did not parallel earlier findings of a beneficial light effect [10,30]. One possibility is that, contrary to our design, these studies challenged sustained attention performance either during light exposure and did not specifically explore carry-over effects or after a prolonged daytime light exposure.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our PVT data did not parallel earlier findings of a beneficial light effect [10,30]. One possibility is that, contrary to our design, these studies challenged sustained attention performance either during light exposure and did not specifically explore carry-over effects or after a prolonged daytime light exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…Evidence for the latter arises from studies in which daytime performance increased after 30 min from light onset [30,31], from an fMRI study in which daytime light enhanced cognitive brain activity during an oddball task [32] and from our previous analysis in which morning light exposure (dawn simulation light) increased wellbeing and enhanced performances across the day [14]. Recently, another study showed the critical role of light for cognitive brain responses in emphasizing the evidence of a cognitive role for melanopsin, which may confer a form of "photic memory" to human cognitive brain function [33].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, subjective alerting and vitalizing effects were expected under high compared to low illuminance levels, and brighter compared to dimmer light conditions were expected to be rated as brighter, more stimulating, and less pleasant [11,16,21].…”
supporting
confidence: 85%
“…Studies on nocturnal light exposure have revealed positive, but also null effects of bright light exposure compared to dim light exposure [9][10][11][12][13]. Results of diurnal studies are even more inconsistent, showing either null, positive, or negative findings of bright as opposed to dim light exposure [7,11,[14][15][16][17][18]. In order to develop more healthy light applications that positively affect our vitality and performance during daytime, it is essential to learn more about underlying mechanisms, including potential moderating and mediating variables, which may explain these inconsistencies.…”
Section: Introductionmentioning
confidence: 99%
“…Light impacts on cognitive performance through its synchronizing/phase shifting effects on the circadian clock or acutely via its alerting effects, as performance (in tasks such as digit recall, serial addition-subtraction and simple reaction time tasks) can immediately improve after the onset of light exposure at night (Badia et al, 1991;Campbell and Dawson, 1990;Foret et al, 1996; and also during the day (Phipps-Nelson et al, 2003;Ruger et al, 2006). EEG and ocular correlates of alertness can vary with cognitive perfor mance, such that EEG alpha (8-12 Hz) and beta (12-20 Hz) activities show a pronounced circadian rhythm with a peak in the second half of the biological day (Cajochen et al, 2002).…”
Section: Neuroanatomical Underpinnings Of the Effect Of Light On Amentioning
confidence: 99%